2018
DOI: 10.1002/cae.21910
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary flipped learning for engineering classrooms in higher education: Students’ motivational regulation and design achievement

Abstract: An interdisciplinary approach can improve both functional and aesthetic design skills for undergraduate engineering students. In this paper, we designed and compared two flipped engineering classrooms, one involving only engineering students who worked on individual design tasks, and the other including groups of an engineering student and an art major student that performed design tasks collaboratively. Fifty‐one engineering students, 29 from the individual flipped classroom and 22 from the interdisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The results shown here can be used for the implementation of innovative activities in university classrooms. Previous studies have shown the motivating effect of university experiences such as gamification [23], Problem-Based Learning [24] and flipped classroom [43]. Thus, Buckley and Doyle showed that gamification in virtual environments had a positive effect on student motivation, although results varied depending on prior motivation [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results shown here can be used for the implementation of innovative activities in university classrooms. Previous studies have shown the motivating effect of university experiences such as gamification [23], Problem-Based Learning [24] and flipped classroom [43]. Thus, Buckley and Doyle showed that gamification in virtual environments had a positive effect on student motivation, although results varied depending on prior motivation [23].…”
Section: Discussionmentioning
confidence: 99%
“…By developing capstone projects, they increased the motivation of both teachers and students. Finally, Park et al found that students' motivations are influenced by the type of activity performed; in their case, they analyzed whether the activities were carried out in an individual or multidisciplinary manner [43].…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, 617 (54%) were in the field of education (for example, Blair et al, 2015;Lundin et al, 2018;Taylor, 2015;Zhai et al, 2017). However, contributions spanned a variety of other fields, including: 245 (22%) in education in scientific disciplines (see Dooley et al, 2013;Mason et al, 2013;Tomory et al, 2015); 58 (5%) in computer science information systems/interdisciplinary applications (see Lin, 2019;Ngoc et al, 2018;Wanner and Palmer, 2015); 40 (4%) in nursing (e.g., Betihavas et al, 2016;Missildine et al, 2013); 35 (3%) in multidisciplinary engineering (see Jo et al, 2018: Park, 2018; 31 (3%) in multidisciplinary and experimental psychology (see Peterson, 2016;Wilson, 2013); 29 (3%) in multidisciplinary chemistry (see Mooring et al, 2016;Shattock, 2016;Wang, 2018); 26 (2%) in pharmacology/pharmacy (e.g., Bossaer et al, 2016;McCabe et al, 2017;Taglieri et al, 2017); 20 (2%) in information science/library science (e.g., Conte et al, 2015;Goates et al, 2017), 24 (2%) in health care sciences (see Bonnes et al, 2017;Chen et al, 2017); 17 (2%) in economics (see Balaban et al, 2016;Calimeris and Sauer, 2015;Grogan, 2017;Gulley and Jackson, 2017;Ficano, 2019) with the remaining articles spanning 93 other disciplines.…”
Section: The Flipped Classroommentioning
confidence: 99%
“…Rapid technological advancement has led to attempts to foster interdisciplinary computing competencies among 21st‐century digital natives with diverse disciplinary backgrounds and computing abilities [11, 13, 39]. Due to the rise of educational robots and the internet of things (IoT), there is an urgent need to train capable instructional designers to meet the job demands in the Fourth Industrial Revolution era.…”
Section: Introductionmentioning
confidence: 99%